Primary Bankart Repair Versus Arthroscopic Anatomic Glenoid Reconstruction in Patients with Subcritical Bone Loss - Zakariya S. Ali, MD; Kednapa Thavorn, BPharm, MPharm, PhD; Ryland Murphy, BSc; Sara Sparavalo, BSc, MASc; Ivan Wong, MD, FRCSC, MAcM, DipSportsMed, FAANA (JBJS Open Access, 2021)
Background:. Anterior shoulder instability and its treatment is a quickly evolving field of interest in orthopaedics, both for patients and for health-care systems. In this study, we aimed to evaluate the cost-effectiveness of arthroscopic anatomic glenoid reconstruction (AAGR) compared with Bankart repair in the treatment of anterior shoulder instability in patients with subcritical glenoid bone loss. Methods:. A cost-utility analysis was performed from the perspective of Canada’s publicly funded health-care system. A decision-tree model was created to simulate the progression of patients undergoing either a primary Bankart repair or AAGR. Recently published data were used to determine the recurrence rate and level of glenoid bone loss for the AAGR procedure; the recurrence rate was 1.4% in a cohort with a mean glenoid bone loss of 25.3%. A literature review on the primary Bankart procedure in patients with at least subcritical levels of glenoid bone loss yielded a recurrence rate of 22.9% in patients with a mean glenoid bone loss of 17.5%. AAGR served as the revision surgery for both primary procedures. Health utility scores for anterior shoulder instability were obtained from published literature. Total procedure costs, including costs of operating-room consumables, anesthesia, diagnostic imaging, and rehabilitation, were sourced from a hospital database. A probabilistic sensitivity analysis using 5,000 Monte Carlo simulations was performed, and results were used to create a cost-effectiveness acceptability curve. Results:. The AAGR procedure was less costly and led to an improvement in quality-adjusted life years (QALYs) when compared with the arthroscopic Bankart repair in the treatment of patients with anterior shoulder instability with subcritical glenoid bone loss (AAGR, cost = $16,682.77 [Canadian dollars] and QALYs = 5.76; Bankart, cost = $16,720.29 and QALYs = 5.46), suggesting that the AAGR is dominant, i.e., lower costs with higher QALYs. Applying a commonly used willingness-to-pay threshold of $50,000 per QALY gained, the probability that the primary AAGR was more cost-effective was 85.8%. Conclusions:. This study showed that, from the perspective of a publicly funded health-care system, AAGR was the economical treatment option when compared with Bankart repair in anterior shoulder instability with subcritical glenoid bone loss. Level of Evidence:. Economic and Decision Analysis Level III. See Instructions for Authors for a complete description of levels of evidence.